1984
DOI: 10.1083/jcb.99.1.260
|View full text |Cite
|
Sign up to set email alerts
|

Intercompartmental transport in the Golgi complex is a dissociative process: facile transfer of membrane protein between two Golgi populations.

Abstract: The transfer of the vesicular stomatitis virus-encoded glycoprotein (G protein) between Golgi populations in fused cells (Rothman, J . E., L. J . Urbani, and R . Brands . 1984 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(51 citation statements)
references
References 27 publications
4
46
1
Order By: Relevance
“…The vesicles which mediate the traffic of the secretory pathway can diffuse throughout the cytosol prior to being consumed at their target organelle (Novick and Schekman, 1979;Rothman et al, 1984) and this traffic continues throughout interphase as long as the donor and target organelle are intact. Vacuole inheritance is also mediated by tubulovesicular traffic (Weisman and Wickner, 1988;Raymond et al, 1992;Gomes de Mesquita et al, 1991) but the bud vacuole is founded at a precise time in the cell cycle by a spatially constrained stream of vesicles and membranous tubules (Weisman and Wickner, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The vesicles which mediate the traffic of the secretory pathway can diffuse throughout the cytosol prior to being consumed at their target organelle (Novick and Schekman, 1979;Rothman et al, 1984) and this traffic continues throughout interphase as long as the donor and target organelle are intact. Vacuole inheritance is also mediated by tubulovesicular traffic (Weisman and Wickner, 1988;Raymond et al, 1992;Gomes de Mesquita et al, 1991) but the bud vacuole is founded at a precise time in the cell cycle by a spatially constrained stream of vesicles and membranous tubules (Weisman and Wickner, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the fragmentation of the Golgi apparatus that occurs in mitosis represents unproductive fusion events. Rothman et al (34) have shown that productive transfer from the Golgi apparatus of one cell to that of another can occur after fusion, so the simple physical separation of Golgi elements that occurs during mitosis need not block transfer. However, the organization of protein and other elements within a Golgi stack or saccule presumably was preserved in the cell fusion experiments, whereas the fragmentation during mitosis could create vesicles that are structurally disorganized or restricted in enzymatic function, thus further reducing the efficiency of productive transfer, or perhaps affecting recognition signals that optimize productive fusions.…”
Section: Discussionmentioning
confidence: 99%
“…Megalocytosis began to develop within 12-18 h and was fully evident by 24 -48 h. Most experiments were performed 4 days after addition of MCTP. In cell fractionation experiments, to avoid detecting proteins that were merely transiting through the Golgi at the time of harvesting the cells, and to thus isolate only the Golgi resident proteins, cultures were pretreated with cycloheximide (10 g/ml) for 2 h (48,53). Cycloheximide inhibits protein synthesis and subsequent entry of any new proteins into the ER-Golgi and thus flushes away secretable proteins from the Golgi (48,53).…”
Section: Methodsmentioning
confidence: 99%